2021
DOI: 10.1126/sciadv.abf0797
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally confined red light-controlled gene delivery at single-cell resolution using adeno-associated viral vectors

Abstract: Methodologies for the controlled delivery of genetic information into target cells are of utmost importance for genetic engineering in both fundamental and applied research. However, available methods for efficient gene transfer into user-selected or even single cells suffer from low throughput, the need for complicated equipment, high invasiveness, or side effects by off-target viral uptake. Here, we engineer an adeno-associated viral (AAV) vector system that transfers genetic information into native target c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…The system is composed of an AAV2 vector attached to PIF6 and an engineered antibody-mimicking DARPin attached to plant phytochrome B. The selectivity of the system is based on the specific cell surface protein binding of the used DARPin and the inactivation of the natural AAV viral tropism, that is, the ability of the virus to infect certain cell types better compared to others ( Hörner et al, 2021 ).…”
Section: Methods Aiding Optogenetics In Neurosciencementioning
confidence: 99%
“…The system is composed of an AAV2 vector attached to PIF6 and an engineered antibody-mimicking DARPin attached to plant phytochrome B. The selectivity of the system is based on the specific cell surface protein binding of the used DARPin and the inactivation of the natural AAV viral tropism, that is, the ability of the virus to infect certain cell types better compared to others ( Hörner et al, 2021 ).…”
Section: Methods Aiding Optogenetics In Neurosciencementioning
confidence: 99%
“…The OptoAAV technology allows the spatially resolved delivery of transgenes into native target cells down to single‐cell resolution by the illumination with low‐intensity red and far‐red light (Hörner et al., 2021). The system is based on an engineered AAV vector of serotype 2 (OptoAAV) and an adapter protein.…”
Section: Commentarymentioning
confidence: 99%
“…To externally control transgene delivery, light is the optimal stimulus as it can be easily applied with high spatiotemporal precision in a reversible manner. As existing technologies for light‐controlled viral gene delivery were hampered by the need for cytotoxic ultraviolet (UV) light (Goater et al., 2000; Ito et al., 2004; Pandori & Sano, 2000; Pandori et al., 2002; Ulrich‐Vinther et al., 2002; Wang et al., 2019), the required uptake of viral vectors to both target and off‐target cells before optical control (Bonsted et al., 2006; Bonsted, Hogset, Hoover, & Berg, 2005; Goater et al., 2000; Gomez, Gerhardt, Judd, Tabor, & Suh, 2016; Hagihara et al., 2020; Hogset et al., 2002; Ito et al., 2004; Tahara et al., 2019; Ulrich‐Vinther et al., 2002; Wang et al., 2019), or the requirement for genetic pre‐engineering of the target cells to express the photoreceptor (Gomez et al., 2016), we recently published the OptoAAV technology that overcomes these limitations (Hörner et al., 2021). The OptoAAV system allows the spatially resolved delivery of transgenes into native target cells upon illumination with low‐intensity red light and is discussed in more detail in the section Background Information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated sequential and spatially defined delivery of different transgenes into native mammalian cell lines and primary cells with single cell resolution. 217 4.1.3.1. Orthogonal Control of Cellular Functions: Combining Photoreceptors of Wavelengths.…”
Section: Transcriptional Gene Expression Controlmentioning
confidence: 99%